2015
DOI: 10.1038/npp.2015.365
|View full text |Cite
|
Sign up to set email alerts
|

Maltreatment Exposure, Brain Structure, and Fear Conditioning in Children and Adolescents

Abstract: Alterations in learning processes and the neural circuitry that supports fear conditioning and extinction represent mechanisms through which trauma exposure might influence risk for psychopathology. Few studies examine how trauma or neural structure relates to fear conditioning in children. Children (n=94) aged 6-18 years, 40.4% (n=38) with exposure to maltreatment (physical abuse, sexual abuse, or domestic violence), completed a fear conditioning paradigm utilizing blue and yellow bells as conditioned stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
223
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(246 citation statements)
references
References 51 publications
(58 reference statements)
7
223
2
2
Order By: Relevance
“…Recent work from our labs is consistent with this prediction, finding atypical fear conditioning among children who experienced environmental threats, including abuse and domestic violence. Children exposed to threat demonstrate poor discrimination of threat and safety cues during fear-conditioning (McLaughlin et al, in press). Whereas children without adversity exposure exhibit stronger fear responses to a stimulus paired with threat compared to one paired with safety, children exposed to threat exhibit fear responses of similar magnitude to threat and safety cues (McLaughlin et al, in press), reflecting either generalization of fear to the safety cue or a generalized problem with associative learning.…”
Section: A Novel Approach: Dimensions Of Adversitymentioning
confidence: 99%
“…Recent work from our labs is consistent with this prediction, finding atypical fear conditioning among children who experienced environmental threats, including abuse and domestic violence. Children exposed to threat demonstrate poor discrimination of threat and safety cues during fear-conditioning (McLaughlin et al, in press). Whereas children without adversity exposure exhibit stronger fear responses to a stimulus paired with threat compared to one paired with safety, children exposed to threat exhibit fear responses of similar magnitude to threat and safety cues (McLaughlin et al, in press), reflecting either generalization of fear to the safety cue or a generalized problem with associative learning.…”
Section: A Novel Approach: Dimensions Of Adversitymentioning
confidence: 99%
“…Across studies, differential conditioning has been observed in these groups of youth [81-83], with some differences emerging for maltreated youth and those with PTSD. Youth who experienced maltreatment exhibited slower differential conditioning as evidenced by a blunted SCR to the CS+ [83]. Additionally, youth with PTSD did not exhibit a differential conditioned SCR when compared to youth without PTSD [83].…”
Section: Threat Conditioning and Extinction In Youth With Ptsd Trmentioning
confidence: 99%
“…Youth who experienced maltreatment exhibited slower differential conditioning as evidenced by a blunted SCR to the CS+ [83]. Additionally, youth with PTSD did not exhibit a differential conditioned SCR when compared to youth without PTSD [83]. In contrast, another study found PTSD symptom severity to have a small-to-moderate association with larger SCRs to the CS+ [82].…”
Section: Threat Conditioning and Extinction In Youth With Ptsd Trmentioning
confidence: 99%
See 2 more Smart Citations